THE CONCEPT OF JIN AND RUQYAH ACCORDING TO THE KOMUNITAS KELUARGA BESAR RUQYAH ASWAJA: THE STUDY OF LIVING QUR’AN - Ardianto, Muhammad (Universitas Nurul Jadid, 2021)
This study aims to describe how ruqyah therapy by KBRA Aswaja in the community in Probolinggo. As a new study, the living Qur’an is scientific research that we do, related to the presence of the Qur’an in a particular Muslim community. With a descriptive-phenomenological method that aims to understand how the culture is in Probolinggo and examine several aspects. In the end, this research resulted in a conclusion that the study of the living Qur’an regarding ruqyah shar’iyyah therapy at the Probolinggo branch of the KBRA showed how apart from living the Qur’an in society as a reading that is worth rewarding, it has also developed into a medium for medical or non-medical treatment. Medical diseases include psychological disorders such as excessive emotional disorders, often fighting parents, often daydreaming, little enthusiasm for life, LGBT, etc. While non-medical in the form of jinn disorders such as frequent trance, heavy shoulders, frequent nightmares, exposure to magic, and others.